Analisis Sistem Pengendalian Internal di Lingkungan Pemerintah Kota Tanjungpinang (Studi Kasus Survei Penilaian Integritas tahun 2024) - Fatahurrazak Fatahurrazak; Hadi Lidya Rikayana Hadi Lidya Rikayana; Nurul Yusyawiru; Fatahuddin (urn:nbn:id:umrah-jafi.v9i1.2025.001jiafi.v9i1, 2025)
This study examines the effectiveness of the internal control system within the Government of Tanjungpinang City using data from the 2024 Integrity Assessment Survey (SPI) conducted by Indonesia’s Corruption Eradication Commission (KPK). The research aims to determine how internal control mechanisms enhance organizational integrity and mitigate corruption risks in local governance. Employing a descriptive–quantitative approach based on secondary SPI data, the analysis applies the five core components of internal control outlined in Government Regulation No. 60/2008: control environment, risk assessment, control activities, information and communication, and monitoring. Statistical and content analyses assess the maturity level of the internal control system and its alignment with KPK’s integrity dimensions. The findings indicate that Tanjungpinang City’s internal control system is at a developing maturity stage, with major weaknesses in leadership commitment, ethical culture, and risk-based monitoring. Despite improvements in transparency and compliance through digital systems, preventive control mechanisms remain limited. The results also show a strong positive relationship between robust internal controls and higher integrity scores, underscoring that strengthening control mechanisms directly promotes institutional integrity. This study emphasizes the importance of integrating risk management into internal control processes, reinforcing ethical leadership, and enhancing the role of internal auditors (APIP) through competency-based training and digital audit tools. These initiatives are crucial for fostering proactive, integrity-oriented local governance. By empirically linking internal control effectiveness with KPK’s SPI framework, this research contributes novel evidence that internal control maturity serves as a predictive indicator of institutional integrity in Indonesia’s public sector